Problematika Pencegahan dan Kejahatan di Bidang Ekonomi - Yanels Garsione Damanik (Jurnal Hukum Lex Generalis, 2020)
Because of the complexity of the problem of crime in the economy, the RKUHP was formed because of the insistence on realizing criminal laws and regulations in accordance with the current and future circumstances and situations. The Criminal Code is currently considered unable to answer the legal vacuum because it cannot be ensnared in various behaviors that harm and threaten the community, but have not been or are not regulated in the Criminal Code. The patchwork system of quick solutions is criticized by various criminal experts as illegal, inconsistent, juridically problematic, and even gnawing, shredding the parent building system. The problem is that the RKUHP does not regulate economic crimes specifically. Some criminal acts related to the economy stipulated in some laws are incorporated into the RKUHP but its formulation is limited to a few categories of criminal acts, namely criminal acts that endanger the environment, corporate liability, criminal acts of falsification of stamps, seals, state stamps, and brands, criminal acts of fraud, and criminal acts of trust in conducting business. Unfortunately, the drafting team is unclear in setting the criteria used to select and/or rule out specific criminal acts outside the Criminal Code into the RKUHP. So it is not clear to what extent the limits of economic crimes are accommodated in the RKUHP. The articles of the RKUHP that regulate some economic crimes are also not spared from problems, especially related to the terms and understandings used in the RKUHP, confusion about some criminal concepts, and duplication. The settings are selected into the RKUHP without synchronizing with other criminal settings so that the arrangement of some criminal acts becomes overlapping. Under these circumstances, the RKUHP will still maintain the existing criminal law system and the purpose of establishing the RKUHP will not be achieved.